The complete practitioner's guide to the bond market - Dym, Steven (New York : McGraw-Hill, 2010)
The book has a wealth of information on a broad range of topics which include risk measures, interest rates swap and corporate bonds
Includes bibliographical references and index.
uaj 24/04/2013
Loans
Keywords: Bond market; Bonds